Nepenthes as Tourism Flagship Species: the Conservation Strategies in Dayak Seberuang Settlements Area - Hendra Setiawan (Journal of Indonesian Tourism and Development Studies, 2017)
The aims of this research are to formulate the conservation strategies of lowland Nepenthes based on conservation status analysis, distribution map, and conceptualizing Nepenthes as flagship species for tourism. Research was held on January to October 2015 in Dayak Seberuang settlement areas, West Kalimantan Province, Indonesia. Literature analysis was used to identify recent conservation status of Nepenthes. Spatial analysis with open access software QGIS ver. 2.4 was used to understand the distribution of Nepenthes. Descriptive analysis and SWOT analysis was used to analyze people perception about Nepenthes. The results showed that from five lowland Nepenthes species which commonly found in West Kalimantan Province, one of them, namely Nepenthes bicalcarata is categorized as vulnerable (VU), and rest of it was categorized as least concern (LC) based on International Union for Conservation of Natural Resources (IUCN). The status of each lowland Nepenthes in West Kalimantan Province is urgent to improve because of much pressure to its population and habitat. Based on the distribution mapping, each Nepenthes has different preference of habitat. Nepenthes bicalcarata can be found only on canopy cover at peat swam forest, on the other hand, N. gracilis and N. mirabilis can be found in open area like Kerangas or secondary forest. Results of SWOT analysis showed that IFAS and EFAS score in range 4.107-4.086 which means that the conservation strategies of lowland Nepenthes in Dayak Seberuang settlements area are in growth phase to improve the Nepenthes population. There are opportunities for the use of Nepenthes as tourism flagship in West Kalimantan.Keywords: community, conservation strategies, Nepenthes.